A quality systems study on San Met - Bo-ot, Jose R.; Ces, Kathy R.; Magno, Cheryl Omega M. (Diliman, Quezon City College of Engineering, 1999)
The main objective of the research was to be able to apply Statistical Process Control tools in San Met. In the same way, a learning process between the researchers and the company (and vice versa) was established. The research process included plant visits to study first hand the production line at work. Interviews were also conducted with top management. All of these data were then subjected to analysis, notably through Ishikawa diagrams, Pareto Charts and Failure Mode Effects and Analysis (FMEA) tables. These charts (as well as the insights obtained on the production of gas stove top plates) were followed by standard control charts. In following the sensitizing rules of control charts, minor revisions were then made to these charts. Further process capability analysis was done, and a quality cost analysis was made. These various processes were then summarized and merged into conclusions and recommendations for the plant. The researchers came to the conclusion that the company's gas stove top plate process is potentially capable to produce products that meet specifications. Yet the process is also not centered, and certain steps may be necessary to further improve quality control in the plant. Such steps are presented as recommendations in the last part of the research.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: San Met; Electric apparatus and appliances; Quality control